Evaluating Global Cybersecurity Laws: Efectiveness of Legal Frameworks and Enforcement Mecanism in the Digital Age - Rusydi, Muhammad Taufik (Walisongo Law Review (Walrev), 2024)
The background of this article highlights the escalating global cybersecurity threats in the digital era and underscores the urgent need to strengthen law enforcement through public–private partnerships (PPPs), as traditional legal frameworks struggle to address the complex and transnational nature of cybercrime effectively. This study examines the role of PPPs in enhancing cyber law enforcement across various legal systems. Using a systematic literature review methodology, the research evaluates the effectiveness of collaborative initiatives between the public and private sectors in combating cyber threats. The findings reveal that PPPs have significant potential to strengthen law enforcement efforts through technological innovation, information sharing, and operational cooperation. However, persistent challenges—such as limited transparency, trust deficits, and conflicting institutional interests—remain substantial barriers to their success. The study recommends that policymakers enhance legal frameworks, promote transparency, and develop capacity-building initiatives through joint training programs. Moreover, the research identifies critical gaps in the existing literature, emphasizing the need for more comprehensive empirical studies to better understand and address the complexities of cyber law enforcement through PPPs in the digital age. Latar belakang artikel ini menyoroti meningkatnya ancaman keamanan siber secara global di era digital serta menegaskan urgensi penguatan penegakan hukum melalui kemitraan publik–swasta. Hal ini diperlukan karena kerangka hukum konvensional sering kali tidak mampu secara efektif menangani kompleksitas dan sifat lintas batas dari kejahatan siber. Penelitian ini bertujuan untuk mengkaji peran PPP dalam meningkatkan efektivitas penegakan hukum siber di berbagai sistem hukum. Dengan menggunakan metode systematic literature review, penelitian ini mengevaluasi efektivitas berbagai inisiatif kolaboratif antara sektor publik dan swasta dalam menghadapi ancaman siber. Hasil penelitian menunjukkan bahwa PPP memiliki potensi besar dalam memperkuat upaya penegakan hukum melalui inovasi teknologi, pertukaran informasi, dan kerja sama operasional. Namun demikian, sejumlah tantangan masih menghambat keberhasilannya, antara lain keterbatasan transparansi, defisit kepercayaan, dan konflik kepentingan antar lembaga. Penelitian ini merekomendasikan agar pembuat kebijakan memperkuat kerangka hukum, meningkatkan transparansi, serta mengembangkan program peningkatan kapasitas melalui pelatihan bersama. Selain itu, penelitian ini juga mengidentifikasi kesenjangan penting dalam literatur yang ada dan menekankan perlunya kajian empiris yang lebih komprehensif untuk memahami dan mengatasi kompleksitas penegakan hukum siber melalui PPP di era digital. Keywords: Cyber Law, Cybersecurity, Public–Private Partnerships, Legal Frameworks, Enforcement Mechanisms.